Outpatient Treatment Trial of Mild and Severe Hypertension. Issue 5804 (1st April 1972) - Stuart, K. L.; MacIver, C.; Nicholson, J. A.
Abstract : Not much is known about the feasibility or the advantages of treatment of subjects with only mild hypertension. There are also many unresolved problems in the outpatient management of hypertension of any severity. In this study an analysis is made of the results of a controlled treatment trial of 56 subjects with mild hypertension, 26 of whom were treated with active drug and 30 initially with placebo, and a treatment programme involving 81 patients with moderate or severe hypertension, all of whom received treatment with active drug. The drugs used in this study were bethanidine, debrisoquine, and guanethidine. Follow-up for 12 months or more was achieved in 87% of individuals admitted to the study with mild hypertension and in 80% with severe hypertension. Many subjects with only mildly raised blood pressure were found to have cardiac enlargement on chest x -ray (up to 45%) and left ventricular hypertrophy on electrocardiogram (up to 51%). Rapid rates of rise of blood pressure were observed in many placebo-treated subjects; but good blood pressure control was achieved in 63 out of 104 patients (61%) receiving active drug in both the mild and the severe hypertension groups. The drugs used showed approximately equal effectiveness in controlling blood pressure.